Impacts of regional trade agreements on international tourism demand: Empirical in Vietnam - Pham Uyen; Quy Trinh; Hoa Le; Uyen Vo (Cogent Economics & Finance, 2023)
This paper sheds some light on the impact of regional trade agreements (RTAs) on international tourism demand in Vietnam. They are using gravity model with data from 29 countries with the highest number of tourists to Vietnam from 2007-2019. The empirical findings indicate a relevant degree of heterogeneity in the results. While the the free trade agreement enhances the international tourism demand in Vietnam, ASEAN community it. These results emphasize the importance of solid integration in promoting Vietnam's tourism flows.
Keywords: 330; ASEAN; FTAs; gravity model; international tourism demand; RTAs